Versatile clinical information system design for emergency departments. - Amouh, T. (IEEE Transactions on information technology in biomedicine)
Compared to other hospital units, the emergency department presents some distinguishing characteristics of its own. Emergency health-care delivery is a collaborative process involving the contribution of several individuals who accomplish their tasks while working autonomously under pressure and sometimes with limited resources. Effective computerization of the emergency department information system presents a real challenge due to the complexity of the scenario. Current computerized support suffers from several problems, including inadequate data models, clumsy user interfaces, and poor integration with other clinical information systems. To tackle such complexity, we propose an approach combining three points of view, namely the transactions (in and out of the department), the (mono and multi) user interfaces and data management. Unlike current systems, we pay particular attention to the user-friendliness and versatility of our system. This means that intuitive user interfaces have been conceived and specific software modeling methodologies have been applied to provide our system with the flexibility and adaptability necessary for the individual and group coordinated tasks. Our approach has been implemented by prototyping a web-based, multiplatform, multiuser, and versatile clinical information system built upon multitier software architecture, using the Java programming language.